2022
DOI: 10.3390/en15020421
|View full text |Cite
|
Sign up to set email alerts
|

A Recent and Systematic Review on Water Extraction from the Atmosphere for Arid Zones

Abstract: Water is essential for food security, industrial output, ecological sustainability, and a country’s socioeconomic progress. Water scarcity and environmental concerns have increased globally in recent years as a result of the ever-increasing population, rapid industrialization and urbanization, and poor water resource management. Even though there are sufficient water resources, their uneven circulation leads to shortages and the requirement for portable fresh water. More than two billion people live in water-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Even in modern society, freshwater shortages and water scarcity continue to be a recurring problem in various parts of the world [34,39,40] despite our perceived distance from these issues. Today, population growth, soaring living standards, global warming, and the uncertainties of climatic variability have already affected water availability, demands, and uneven water distribution, causing more than two billion people to live in waterdeficient areas or during water crises [41,42]. Different strategies and dedicated materials were researched for water extraction from atmospheric air devoted to the enhancement of water productivity and versatility in applications [30][31][32][33][34][43][44][45][46][47] particularly in arid regions for the alleviation of water scarcity [42].…”
Section: Discussionmentioning
confidence: 99%
“…Even in modern society, freshwater shortages and water scarcity continue to be a recurring problem in various parts of the world [34,39,40] despite our perceived distance from these issues. Today, population growth, soaring living standards, global warming, and the uncertainties of climatic variability have already affected water availability, demands, and uneven water distribution, causing more than two billion people to live in waterdeficient areas or during water crises [41,42]. Different strategies and dedicated materials were researched for water extraction from atmospheric air devoted to the enhancement of water productivity and versatility in applications [30][31][32][33][34][43][44][45][46][47] particularly in arid regions for the alleviation of water scarcity [42].…”
Section: Discussionmentioning
confidence: 99%
“…Rang Tu and Yunho Hwang concluded that water productivity using VCR technologies lays in the range of 0.13-4.20 L/h and SEC is in the range of 0.18-2.08 kWh/L at air flow rate of 300-1000 m 3 /h. Smaller value can be seen in literature, depending on the size of the device used and the cooling power, 250 mL have been achieved in 1.5 hours [13]. Kwan et al in 2020 has experimented a hybrid system for AWH, this system depends on using a fuel cell to power a VCR machine for harvesting atmospheric water and add the fuel cell (FC) productivity to the VCR AWH productivity; up to 3 L/h of freshwater when RH = 75% with 2 kW FC, which is 50% higher than excluding the FC [14].…”
Section: Literature Surveymentioning
confidence: 92%
“…Black cotton saturated with calcium chloride and recycling the latent heat by using dual stage device were analyzed [29,30]. Many other studies have been done on sorption technique with various desiccants and various ways of water collection including dual cycle with VCC for water collection [31,32]. All of these methods are suffering from the high energy consumption, thus high cost of water productivity.…”
Section: Literature Surveymentioning
confidence: 99%
“…Water is the indispensably precious resource that mankind depends on for existence and development [ 1 ]. By the year 2025, the number of people who lack access to safe drinking water is estimated to be more than 2 billion; nearly 20% of the global population will be living in countries or regions with absolute water scarcity [ 2 , 3 ]. Unfortunately, rapid economic development, industrialization, and urbanization have exacerbated water shortages and water quality degradation.…”
Section: Introductionmentioning
confidence: 99%